Tempo de jejum pré-operatório realizado em hospitais brasileiros : estudo multicêntrico - Dias, Ana Laura de Almeida (2014)
Background: Prolonged fast increases the organic response after trauma. This multicenter study investigated the difference between the prescribed and the actual preoperative fasting time in Brazilian hospitals. Methods: We initially invited researchers from 25 Brazilian hospitals to include in this study, patients candidates for elective surgery between August 2011 and September 2012. The variable of primary interest was the difference between the time of fasting prescribed and executed. Other variables collected were sex, age, surgical disease (malignancies or benign disease), operation type, ASA (American Society of Anesthesiologists) physical status score, type of hospital (public or private) and the nutritional status. Results: Only 16 of the 25 invited hospitals sent data. The data of 3,715 patients (58.1% females) with median age of 49 (18-94) years-old from hospitals in all regions of the country were analyzed. The median (range) time of preoperative fast was 12 (2-216) h. This time was greater (p < 0.001) in 12 hospitals that still using traditional fasting protocol (13 [6-216] h) than in 4 others that had already adopted new fasting guidelines (8 [2-48] h). The vast majority (n = 2,962; 79.4%) of the patients were operated on bearing greater than 8h of fast and 46% (n = 1,718) with more than 12h. There was no influence of ASA physical score, age, sex, type of surgery, and type of hospital in the observed fasting time. Patients operated on due to a benign disease had a preoperative fasting time longer than those for cancer. Conclusion: The duration of preoperative fasting in Brazilian hospitals studied is greater than the prescribed. Most of these hospitals still adopt traditional rather than modern fasting guidelines and these the fasting time is longer. All patients are remained at risk for long periods of fasting, independent of the variables studied. Patients undergoing surgery for benign disease probably have increased risk of prolonged fasting.